Gambaran Pengelolaan Logistik Non Medis di Rumah Sakit Islam Ibnu Sina Bukittinggi Tahun 2025 - Salsabila Amani Fathiha; Erpidawati, Erpidawati; Elsi Susanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study addresses the issue of unit delays in providing goods receipt notes and routine distribution of supplies to the general logistics department, which impacts the inefficiency of the non-medical logistics management process at Ibnu Sina General Hospital, Bukittinggi. Untimely logistics management can hamper the availability of goods, disrupt the smoothness of services, and increase the risk of stock outs. The purpose of this study is to obtain a comprehensive overview of non-medical logistics management at the hospital, particularly in the aspects of planning, procurement, and control. The research method used is descriptive qualitative with in-depth interviews with five informants. The research informants include Mrs. D as triangulation, Mr. Y and Mr. B as general logistics staff, and Mrs. D and Mrs. S as unit staff. Data were analyzed to identify patterns and obstacles that occur in the non-medical logistics management process. The results show that the entire non-medical logistics management process at Ibnu Sina General Hospital, Bukittinggi is guided by requests from the unit. Logistics planning is carried out based on the receipt notes submitted by the unit, procurement can only be carried out after the receipt notes are received, and stock control is carried out by summarizing requests in the stock card. Although the procedures complied with the Standard Operating Procedures (SOPs) established by the hospital director, obstacles were identified, including delays in unit submissions and weak stock control at the unit level. This situation has the potential to lead to management inefficiencies and stockouts. The conclusion of this study confirms that the non-medical logistics management system at Ibnu Sina Islamic Hospital, Bukittinggi, complies with SOPs. However, improvements in timeliness in submitting orders and strengthening stock control within the units are needed to optimize logistics management efficiency.